“Motile-targeting” drug delivery platforms based on micro/nanorobots for tumor therapy - Zhang, Di; Liu, Shuyi; Guan, Jianguo; Mou, Fangzhi (Frontiers in Bioengineering and Biotechnology, 2022)
Traditional drug delivery systems opened the gate for tumor-targeted therapy, but they generally took advantage of enhanced permeability and retention or ligand-receptor mediated interaction, and thus suffered from limited recognition range (<0.5 nm) and low targeting efficiency (0.7%, median). Alternatively, micro/nanorobots (MNRs) may act as emerging “motile-targeting” drug delivery platforms to deliver therapeutic payloads, thereby making a giant step toward effective and safe cancer treatment due to their autonomous movement and navigation in biological media. This review focuses on the most recent developments of MNRs in “motile-targeting” drug delivery. After a brief introduction to traditional tumor-targeted drug delivery strategies and various MNRs, the representative applications of MNRs in “motile-targeting” drug delivery are systematically streamlined in terms of the propelling mechanisms. Following a discussion of the current challenges of each type of MNR in biomedical applications, as well as future prospects, several promising designs for MNRs that could benefit in "motile-targeting" drug delivery are proposed. This work is expected to attract and motivate researchers from different communities to advance the creation and practical application of the "motile-targeting" drug delivery platforms.